2010
DOI: 10.2478/v10003-010-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Active Faulting and Deformation of Quaternary Landform Sub-Himalaya, India

Abstract: Landforms developed across terrain defining boundary the Main Boundary Thrust (MBT) have imprints of recent tectonic activity. Depositional landforms such as colluvial fan bear signatures of later phases of tectonic activity in the form of faulting of colluvial fan deposits and development of fault scarps. Tectonic geomorphology applied to the MBT zone suggests recent subsurface activity along the MBT and its splay thrusts. Present day tectonic activity of MBT is indicated by ground creeping, thrusting of Lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Banerjee et al (1999), in the Kumaun Himalaya, reported out-of-sequence thrust activity in the Nainital region at c. 40 ka at the Nainital Fault and the Sleepy Hollow Fault, and at the MBT c. 70 ka. Around 10 -30 m vertical displacement of terraces was observed in the Nainital region (see also Kothyari et al 2010). The Bhikiyasain Fault is a steeply dipping/sub-vertical transverse neotectonic fault from the Almora region of unknown exact timing (Goswami & Pant 2008b).…”
Section: Lesser Himalayamentioning
confidence: 99%
“…Banerjee et al (1999), in the Kumaun Himalaya, reported out-of-sequence thrust activity in the Nainital region at c. 40 ka at the Nainital Fault and the Sleepy Hollow Fault, and at the MBT c. 70 ka. Around 10 -30 m vertical displacement of terraces was observed in the Nainital region (see also Kothyari et al 2010). The Bhikiyasain Fault is a steeply dipping/sub-vertical transverse neotectonic fault from the Almora region of unknown exact timing (Goswami & Pant 2008b).…”
Section: Lesser Himalayamentioning
confidence: 99%
“…In the Himalaya, the localized normal faulting is reported from various terrains of the Himalaya from the Higher Himalaya up to the HFT zone, where HFT is the youngest crustal boundary where at present is the zone of maximum convergence (Thakur 2004;Thakur et al 2009). In the MBT zone, recent movement along this intra-crustal boundary is characterized by thrusting of the older bedrocks over the younger sediments (Thakur et al 2009;Kothyari et al 2010). In the frontal part, the compressional characteristic of the HFT is defined by thrusting of the Siwalik rocks over the Gangetic alluvia, uplift terrace, tilted terrace and fault scarps.…”
Section: Discussionmentioning
confidence: 98%
“…Uplift and incision of bedrock and formation of strath terraces, fill terraces, debris‐flow terraces, and fossil valleys associated with epigenetic gorges are the common morphotectonic features observed within the different thrust zones along the Kali River valley. The morphotectonic setting together with the earthquake activities suggests that the study area is tectonically active and the drainage patterns are a consequence of ongoing tectonic activity associated with the MCT, AT, BjT, BT, NAT, MBT, and HFT (Kothyari, ; Kothyari et al, ; Kothyari et al, ; Luirei et al, ; Pant et al, ). Furthermore, Mukul, Jaiswal, and Singhvi (); Wobus, Heimsath, Whipple, and Hodges (); and Wobus et al () believed that the hinterland thrusts are active ~30 km south of the MCT within the Lesser Himalaya, which is marked by the abrupt elevation changes.…”
Section: Combined Discussionmentioning
confidence: 99%
“…Further downstream, the Kali River flows across the Main Boundary Thrust (MBT) zone. The steeply inclined thrust plane has brought Lesser Himalayan rocks upon the Cenozoic sedimentary terrain of the Outer Himalaya (Kothyari et al, ; Kothyari, Pant, Joshi, Luirei, & Malik, ; Valdiya, ). However, towards the Himalayan front, the river flows across the Himalayan Frontal Thrust (HFT), which defines the southern limit of the Himalaya against the Indo‐Gangetic Plains of Quaternary age.…”
Section: Generalized Geology and Structurementioning
confidence: 99%